Efek Infeksi Virus SARS-CoV-2 Pada Organ - Rani Himayani; Helmi Ismunandar; Aulia Khairunnisa; Gayitri Humaera; Meilisa Hidayah Putri; Novi Jayanti (CV. Jasa Sukses Abadi, 2021)
In December 2019, an outbreak of viral pneumonia caused by a novel coronavirus (since named SARS-CoV-2) was identified in Wuhan, China. Within few months, this disease known as coronavirus disease 2019 (COVID-19) spread worldwide, causing a global health emergency. The classic routes for transmission of SARS-CoV-2 are airborne droplets and surface contamination. The clinical presentation of COVID-19 ranges from asymptomatic infection to severe respiratory failure, with fever, fatigue, and cough occurring in most cases. The pathophysiology of SARS-CoV-2 infection is complex, endotoxin and tumor necrosis factor (TNF-α) trigger the production of interleukin (IL)-6 and IL-8, which is followed by a cytokine storm. Moreover, SARS-CoV-2 binds to angiotensin-converting enzyme-2 (ACE2) receptors, which are widely distributed not only in the lung alveolar epithelial cells and nasopharyngeal and oral mucosa but also in the endothelium and vascular smooth muscle cells, in the brain, in the gut, and in peripheral organs such as the liver and kidneys. This suggests that the clinical spectrum of COVID-19 is not limited to local pneumonia, but rather represents a multisystem illness with involvement of different organs and potential for systemic complications. Keywords:Covid-19, Angiotensin-converting enzyme, Multiple Organs.